Emerging and potential trends in public management an age of austerity - Diamond, John, 1954-; Liddle, Joyce, 1952- (Critical perspectives on international public sector management,, 2012)
Challenging some of the established practices of public policy and administration, which have been called into question in recent years by the financial and banking crises of 2008, the authors specifically seek to investigate current public sector management and the public managers acting in the interests of civil society to get to the heart of best practice.